(A Study The removing Technique of Beany Flavour in Soybean Flour Processing) - Sofiyah, Siti; Utami, Sri (Balai Besar Industri Agro, 1990)
Effect of soaking in Na HCO3 1 % solution and steaming on soy flour product have been studied. Steamed soy was pressed using expeller to minimize the oil content of soy flour. The result of organoleptic test showed that the best flour could be produced by soaking in Na HCO3 1% combined with steaming 15.